Analytical approach for kinematic FCRW–soil interaction in multi–layered soil under earthquake loads. Issue 162 (November 2022) - Ke, Wenhai; Li, Yuan; Chen, Qingsheng; Pain, Anindya; Hu, Yun
Abstract: A closed form solution for FCRW (flexible cantilever retaining wall)–soil interaction under seismic condition is proposed for a layered soil profile. The displacement function of the FCRW and the attenuation function of the kinematic FCRW–soil interaction are obtained in the coupled form based on the Hamilton's principle. Then an iterative procedure is applied to solve the coupled functions. There are three main contributions of the proposed model: (1) the kinematic FCRW response in layered soil system is analyzed based on an analytical method; (2) the soil continuity effect is taken into account; (3) the kinematic FCRW–soil interaction in layered soil is quantitatively analyzed. The results highlight that the soil stiffness discontinuity significantly influences the contribution of the different physical mechanisms (e.g., FCRW rigidity, Winkler spring and soil continuity) in kinematic FCRW–soil interaction. The results also show that the soil stiffness discontinuity may exponentially amplify the seismic earth pressure and kinematic FCRW response. Highlights: The kinematic FCRW response in layered soil system is analyzed based on an analytical method. Compared with the existing continuum models, which mainly focuses on the kinematic FCRW response in homogeneous soil, this paper further quantitatively analyzed the physical mechanisms in kinematic FCRW-soil interaction and reveals the influence of the soil layered characteristic on the kinematic FCRW response.